In an Unpredictable and Changing Environment: Intrapreneurial Self-Capital As a Key Resource for Life Satisfaction and Flourishing - Di Fabio, Annamaria; Palazzeschi, Letizia; Bucci, Ornella (Frontiers in Psychology, 2017)
The 21st century is characterized by an unpredictable and challenging work environment, and the Intrapreneurial Self-Capital (ISC) career and life construct can be seen as a core of individual intrapreneurial resources that enables people to cope with ongoing challenges, changes, and transitions founding innovative solutions when confronted with the constraints imposed by such an environment. The ISC is a challenging construct since it can enhance behavior and attitudes through specific training, unlike personality traits, which are considered substantially stable in the literature. Against this background, the present study examined the relationship between ISC and well-being (hedonic well-being and eudaimonic well-being) controlling for the effects of personality traits. The Big Five Questionnaire (BFQ), the Intrapreneurial Self-Capital Scale (ISCS), the Satisfaction With Life Scale (SWLS), and the Flourishing Scale (FS) were administered to 258 Italian workers. Hierarchical regression analyses showed that ISC explained a percentage of incremental variance beyond that explained by personality traits in relation to both life satisfaction and flourishing. These results indicate that ISC is a key resource for hedonic well-being and eudaimonic well-being and that it offers new research and intervention opportunities.